(untitled) (Philippine Journal of Agricultural Economics, 2019)
This study was conducted to test and compare the seedling vigor performance of dwarf green and dwarf white varieties of tomato as affected by two methods of seed extraction such as fermentation and hydrochloric acid in terms of germination percentage, germination rate, days to seedlings emergence, days to 50% development of true leaves, root length, stem length and shoot length. It was carried using Complete Randomized Design (CRD) in a 2x2 factorial experiment with four treatment combinations with three replications. Dwarf Green variety was affected by seed method extraction with HCl treatment had ideal conditions for seed and seedling quality performance and vigor of tomato such as germination percentage and rate, number of days to seedling emergence, number of days to fifty percent development of true leaves, root, stem and shoot length. Dwarf White performed inferior than Dwarf Green in terms of the parameters investigated.